2014
DOI: 10.12659/msm.889862
|View full text |Cite
|
Sign up to set email alerts
|

Research on the occurrence of Mycobacterium tuberculosis antigens in the circulating immune complexes, isolated from serum of patients with tuberculosis

Abstract: BackgroundTuberculosis is one of the most dangerous infectious diseases and has among the highest mortality rates of all infectious diseases. There are 9 million cases of active tuberculosis reported annually; however, an estimated one-third of the world’s population is infected with Mycobacterium tuberculosis and remains asymptomatic. Despite the great progress in its diagnosis and treatment, tuberculosis is still a serious health and social problem. The contact between the immune system and Mycobacterium tub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Serum was collected and stored at −80°C till further use. ICs were isolated using Przybylski and Gołda 10 method using 7 per cent polyethylene glycol. The absorbance was read at 280 nm and 260 nm using a spectrophotometer and total protein concentration was estimated using 280/260 nm ratio 9 .…”
Section: Methodsmentioning
confidence: 99%
“…Serum was collected and stored at −80°C till further use. ICs were isolated using Przybylski and Gołda 10 method using 7 per cent polyethylene glycol. The absorbance was read at 280 nm and 260 nm using a spectrophotometer and total protein concentration was estimated using 280/260 nm ratio 9 .…”
Section: Methodsmentioning
confidence: 99%
“…Their importance is well established in renal diseases [6]; inflammatory disorders such as rheumatoid arthritis [7] and systemic lupus erythematosus; infectious diseases such as dengue, sclerosing panencephalitis, hepatitis and malignancies [5,8]. Although many studies report identification of ICs during disease processes, only a few have reported identification of antigens within ICs [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%